Analisis Kehilangan Minyak (Oil Losses) Pada Proses Pengolahan CPO (Crude Palm Oil) Dengan Metode SPC (Statistical Proces Control) Studi Kasus di PT. Pabrik Nusantara (PTPN) 6 Solok Selatan - Ernita; Gamindra Jauhari; Tri Maiyuni Helia (SAINTEK : Jurnal Ilmiah Sains dan Teknologi Industri, 2018)
In every manufacturing and service companies have their own provisions in running the company. Likewise with PTPN VI Solok Selatan, this company is managed by the state (SOE/STATE-OWNED ENTERPRISES) which produces two types of products namely Crude Palm Oil (CPO) and Karnel (core). In its production process, the PTPN 6 Solok Selatan palm oil mill attempts to optimize the yield and improve product quality. Thus the South Solok oil palm plant is certainly trying to lose oil (oil losses) occur to a minimum. Quality control is statistically performed using statistical tools contained in statistical proces control (SPC). Statistical Process Control (SPC) is an analytical decision-making method that shows a process running well or not (Zagloel & Nurcahyo, 2013). Statistical Process Control (SPC) is used to monitor the consistency of processes used for the manufacture of designed products with the aim of obtaining controlled processes. Comparison of oil losses against normal conditions that exceeded the standard in the period July to December 2017, tankos of 0.77%, press 0.12%, nut by 0.02% and fat fit of 0.08%. Of the four measurements there is one measurement that is beyond the control limits that is on the nut, which resulted in oil losses there are four factors that influence the factors of HR, Machinery, Materials and Methods.